Droplet counter-current chromatography of indole alkaloids from Tabernaemontana hilariana - Lima Cardoso, Claudia Andrea [UNESP]; Vilegas, Wagner [UNESP] (My University, 1999)
This paper reports the separation of the indole alkaloids from the benzene extract of the root barks of Tabernaemontana hilariana (Apocynaceae). The crude alkaloid fraction was fractionated by droplet counter-current chromatography using a low polarity mixture (hexane:ethyl acetate:ethanol:water). Nine indole alkaloids (3-hydroxycoronaridine, coronaridine, voacangine, 3-(2-oxopropyl) coronaridine, voacangine hydroxyindolenine, ibogamine, voacangine pseudoindoxyl, coronaridine pseudoindoxyl and tabernanthine) were identified using thin layer chromatography, gas chromatography coupled with mass spectrometry and nuclear magnetic resonance spectroscopy.
Keywords: Apocynaceae; Droplet counter-current chromatography; Indole alkaloids; Tabernaemontana hilariana